Endocannabinoid System: Chemical Characteristics and Biological Activity - Bismarck Rezende; Allan Kardec Nogueira Alencar; Graziele Freitas de Bem; Fabrícia Lima Fontes-Dantas; Guilherme Carneiro Montes (MDPI AG, 2023)
The endocannabinoid system (eCB) has been studied to identify the molecular structures present in Cannabis sativa. eCB consists of cannabinoid receptors, endogenous ligands, and the associated enzymatic apparatus responsible for maintaining energy homeostasis and cognitive processes. Several physiological effects of cannabinoids are exerted through interactions with various receptors, such as CB1 and CB2 receptors, vanilloid receptors, and the recently discovered G-protein-coupled receptors (GPR55, GPR3, GPR6, GPR12, and GPR19). Anandamide (AEA) and 2-arachidoylglycerol (2-AG), two small lipids derived from arachidonic acid, showed high-affinity binding to both CB1 and CB2 receptors. eCB plays a critical role in chronic pain and mood disorders and has been extensively studied because of its wide therapeutic potential and because it is a promising target for the development of new drugs. Phytocannabinoids and synthetic cannabinoids have shown varied affinities for eCB and are relevant to the treatment of several neurological diseases. This review provides a description of eCB components and discusses how phytocannabinoids and other exogenous compounds may regulate the eCB balance. Furthermore, we show the hypo- or hyperfunctionality of eCB in the body and how eCB is related to chronic pain and mood disorders, even with integrative and complementary health practices (ICHP) harmonizing the eCB.